Metal‐Based Nanomaterials in Biomedical Applications: Antimicrobial Activity and Cytotoxicity Aspects. (17th March 2020) - Makvandi, Pooyan; Wang, Chen‐yu; Zare, Ehsan Nazarzadeh; Borzacchiello, Assunta; Niu, Li‐na; Tay, Franklin R.
Abstract: Microbial colonization on material surfaces is ubiquitous. Biofilms derived from surface‐colonized microbes pose serious problems to the society from both an economical perspective and a health concern. Incorporation of antimicrobial nanocompounds within or on the surface of materials, or by coatings, to prevent microbial adhesion or kill the microorganisms after their attachment to biofilms, represents an important strategy in an increasingly challenging field. Over the last decade, many studies have been devoted to preparing meta‐based nanomaterials that possess antibacterial, antiviral, and antifungal activities to combat pathogen‐related diseases. Herein, an overview on the state‐of‐the‐art antimicrobial nanosized metal‐based compounds is provided, including metal and metal oxide nanoparticles as well as transition metal nanosheets. The antimicrobial mechanism of these nanostructures and their biomedical applications such as catheters, implants, medical delivery systems, tissue engineering, and dentistry are discussed. Their properties as well as potential caveats such as cytotoxicity, diminishing efficacy, and induction of antimicrobial resistance of materials incorporating these nanostructures are reviewed to provide a backdrop for future research. Abstract : Different types of metal‐based nanostructures and their applications in biomedical fields, antimicrobial activity, and their cytotoxicity aspects are described here. In addition, the potential development of nanometals and the problems facing them in the future are comprehensively presented, hoping to trigger exchanges and discussions from all fields of scientists.